Institutional Pressure and Business Sustainable Performance: Does Environmental Management Accounting Matter? - Kadir M.R.A.; AlBalushi A.R.S.I.; Javed S. (Sage Publications India Pvt. Ltd, 2025)
This study investigates the relationship between institutional pressures (IP) and sustainable business performance (SP) within Oman?s industrial sector, emphasizing on the mediating role of environmental management accounting (EMA). Drawing from the institutional theory, a sample of 307 respondents from Oman-based manufacturing firms listed on the Muscat Stock Exchange was considered. Data were gathered via an online questionnaire directed at accounting and finance professionals, with an impressive response rate of 96%. Using structural equation modelling through SPSS and AMOS, the analysis revealed that coercive pressure has a positive yet insignificant influence on SP, while normative pressure significantly correlates with SP. Additionally, while most dimensions of IP positively influence EMA, normative pressure was found to have no significant relationship with EMA. The results further confirm the significant positive impact of EMA on SP. This study underscores the pivotal role of EMA in fostering a sustainable business environment in Oman, accentuating the need for environment-friendly policies driven by IP. ? 2024 Indian Institute of Management Kozhikode.